Pengaruh Moderasi Profitabilitas Pada Hubungan Multinasionalitas dan Transfer Pricing Terhadap Penghindaran Pajak - Nugroho, Arif Dwi; Agung Sasangka, Luhur Wicaksana; Reskino, Reskino (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2024)
Palm oil companies' tax revenues have declined over the past decade despite increased production, indicating tax avoidance. The research focuses on exploring the link between multinationality, transfer pricing, and tax avoidance. Using panel data regression analysis with Eviews, the author analyzes financial reports from palm oil issuers on the Indonesia Stock Exchange from 2011 to 2018. The sample comprises 112 data points selected from a population of 240, based on specific criteria. Results indicate that multinationality has a positive and significant effect on tax avoidance. On the other hand, transfer pricing does not have a significant effect on tax avoidance. In addition, profitability cannot significantly moderate the relationship between multinationality and tax avoidance or between transfer pricing and tax avoidance.